Peran Pemerintah Dalam Pendidikan Anak Suku Togutil - Telly Muriany; Victor Ruhunlela (Univiversitas Dr. Djar Wattiheluw, 2024)
The study aims to analyze and describe the role of government in the education of Togutil children in Baburino village, Maba sub- district, East Halmahera district, and North Maluku province. This study is a descriptive- qualitative study. The informants for this study were five people who were determined to use deliberate techniques. The data collection techniques used were observation, interviews, and notes, and the analysis techniques used were data reduction, data presentation, and drawing conclusions. The results show: 1) The government's role in educating Togutil children is very good now because the government is trying to build education in Baburino village, create conditions for Togutil children of Baburino village to 'go to school in the neighboring village, and prepare formal educational facilities for Togutil children. 2) Factors that can influence the role of government in the education of Togutil children in Baburino village, Maba sub-district, East Halmahera district, and North Moluccas province are school facilities and infrastructure, socialization factors, and economic factors.